Paternal or maternal uniparental disomy of chromosome 16 resulting in homozygosity of a mutant allele causes Fanconi anemia - Donovan, Frank X. (Hum Mutat, 2016)
Fanconi anemia (FA) is a rare inherited disorder caused by pathogenic variants in one of 19 FANC genes. FA patients display congenital abnormalities, and develop bone marrow failure, and cancer susceptibility. We identified homozygous mutations in four FA patients and, in each case, only one parent carried the obligate mutant allele. FANCA and FANCP/SLX4 genes, both located on chromosome 16, were the affected recessive FA genes in three and one family respectively. Genotyping with short tandem repeat markers and single nucleotide polymorphism (SNP) arrays revealed uniparental disomy (UPD) of the entire mutation-carrying chromosome 16 in all four patients. One FANCA patient had paternal UPD, whereas FA in the other three patients resulted from maternal UPD. These are the first reported cases of UPD as a cause of FA. UPD indicates a reduced risk of having another child with FA in the family and has implications in prenatal diagnosis.